Protection Strategies on Irrigated Farm Using Analytic Hierarchy Process - Pramana, Novi; Prajanti, Sucihatiningsih Dian Wisika (Muhammadiyah University Press, 2018)
Semarang District is an area which one of its focuses is on improving regional economy mainly based on agricultural sector. The agricultural activities which still depend on lands make those are considered having an important role. It is supported with regulations which protect the functional changes of farm lands, especially the irrigated ones. However, during a period of 2010-2014, the irrigated farm lands were reduced. A strategy to protect those irrigated farm lands is highly necessary, that is, by considering criteria to prioritize on protection of the irrigated farm lands in Semarang district. This study uses a method of Analysis Hierarchi Process (AHP) with a purposive sampling technique to collect 10 respondents. A protection strategy on Irrigated farm lands in Semarang district consists of several criteria with a prioritized program criterion of sustainable land and water utilization (0.322). The following criteria are optimization of irrigation network performance (0.241), law (0.186), economy (0.160), and social (0.091). There are some suggestions after conducting this study, such as providing education and socialization of legislations of law on farm land protection especially the irrigated ones, construction of reservoirs and dams, utilization of organic materials on farm lands management, irrigation network rehabilitation, strengthening legislations on protection of farm lands, authorities’ closer controls and supervisions, facilitation in obtaining agricultural inputs to improve welfare by empowering families, owners, and managers of those irrigated farm lands, as well as escorting policies on layout and regional plans to maintain the wide agricultural areas of irrigated farm lands.